2007
DOI: 10.1080/15391523.2007.10782484
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effectiveness of the Louisiana Algebra I Online Course

Abstract: Student enrollment in K-12 online learning programs showed a tenfold expansion in the years between 2002 and 2005. Despite increased implementation to fulfill critical local needs, there is very little evidence-based research available to inform education leaders' decisions relating to these initiatives. To address the important question of whether online learning can be as effective as traditional face-to-face learning, this research presents the findings from a quasi-experimental design implemented to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 16 publications
5
35
0
3
Order By: Relevance
“…Their responses indicated that learning with Bl model gave another benefit, it could improve their interest and motivation as it was said by Barbour & Reeves (2009), grow students' independent learning, as said by Parkes et al, (2011), and improve students' ICT skill, as stated by O'Dwyer et al, (2007).…”
Section: Product Validitymentioning
confidence: 94%
See 1 more Smart Citation
“…Their responses indicated that learning with Bl model gave another benefit, it could improve their interest and motivation as it was said by Barbour & Reeves (2009), grow students' independent learning, as said by Parkes et al, (2011), and improve students' ICT skill, as stated by O'Dwyer et al, (2007).…”
Section: Product Validitymentioning
confidence: 94%
“…Some researchshowed that BL had many advantages like increasing flexibility (Pratt & Trewern, 2011), increasing effectiveness and students' motivation (Barbour & Reeves, 2009), growing students' independence in learning (Parkes et al, 2011), and improving students' ICT skill (O'Dwyer et al, 2007). Compared to the pureface-to-facelearning or pure e-learning/online learning, BL is said to be more effective (Means et al, 2009) students joining BL model have better performance than those following traditional learning method (Yapici & Akbayin, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting results were obtained in the other large-scale K-12 study, conducted by O'Dwyer, Carey and Kleiman (2007). These investigators used a quasi-experimental design to compare the learning of students participating in the Louisiana Algebra I Online initiative with the learning of students in comparison classrooms that were "similar with regard to mathematics ability, environment, and size, but where teachers used traditional 'business as usual' approaches to teaching algebra" (p. 293).…”
Section: Exhibit 7 Studies Of Online Learning Involving K-12 Studentsmentioning
confidence: 90%
“…Of the 99 studies, only nine were conducted with K-12 students (Chang 2008;Englert et al 2007;Long and Jennings 2005;O'Dwyer, Carey and Kleiman 2007;Parker 1999;Rockman et al 2007;Stevens 1999;Sun, Lin and Yu 2008;Uzunboylu 2004). Of them, four were excluded from the meta-analysis: Chang (2008), Parker (1999), and Uzunboylu (2004) did not provide sufficient statistical data to compute effect sizes, and the Stevens (1999) study was a quasiexperiment without a statistical control for potential existing differences in achievement.…”
Section: Effect Size Extractionmentioning
confidence: 99%
“…With regard to the use of computers for differentiated instruction, previous research has shown that student achievement can increase as a result of blended learning (Englert et al 2007;O'Dwyer, Carey, & Kleiman, 2007), but research has not focused on other outcomes, such as how faculty and staff perceptions change as a result of implementing a blended learning approach. Teacher knowledge and beliefs are important factors that have been shown to contribute to outcomes such as student motivation and student achievement (Woolfolk Hoy, Davis, & Pape, 2006).…”
Section: Background: School Improvement and Blended Learningmentioning
confidence: 99%